The politics of death: multiculturalism and the afterlives of muslims in Europe - Becker-Topkara, Elisabeth; Arana Barbier, Paula Maria (Ethnicities, 2025)
In this special issue, we examine the politics of death through a multicultural lens, focusing on empirical examples that help us to sharpen theories of inclusion and exclusion in Europe. We propose the politics of death as a multidimensional concept centred around processes of recognition and accommodation, which are shaped by (legal) regulations and cultural and religious norms. While both recognition and accommodation have been theorized and empirically explored by contemporary scholars of multiculturalism across the social sciences and humanities, they have focused on the lived experiences of plural populaces in contemporary Europe. We focus instead on what happens to minoritized populations in Europe after they die. Taking into account the management and trajectories of dead bodies allows us to investigate the context-specificity of both recognition and accommodation in plural European societies.